2321. Epidemiology of Staphylococcus aureus Infections in Patients Admitted to Freestanding Pediatric Hospitals, 2009–2016. (26th November 2018) - Spaulding, Alicen B; Thurm, Cary; Courter, Joshua; Banerjee, Ritu; Gerber, Jeffrey S; Newland, Jason; Parker, Sarah; Brogan, Thomas; Kronman, Matthew; Shah, Samir; Smith, Michael; Patel, Sameer; et al.
Abstract: Background: S. aureus causes a substantial number of pediatric infections in the United States each year, with potential for severe complications including death. Recent data suggest S. aureus infections are declining in adults, but a nationally representative and contemporary characterization of trends in pediatric S. aureus infections is lacking. Our objective was to describe recent pediatric hospitalization trends for S. aureus and associated antibiotic prescribing patterns. Methods: We conducted a retrospective cohort study using Pediatric Health Information Systems data from 39 tertiary care freestanding children's hospitals in the United States. All inpatient encounters for patients ages <18 hospitalized between 1/1/2009–12/31/2016 at a continuously reporting hospital were included. Analysis was limited to patients with S. aureus infection, defined as: 1) having ≥1 ICD discharge code for methicillin-resistant (MRSA) or methicillin-susceptible (MSSA) S. aureus ; and 2) ≥1 anti-staphylococcal antibiotic received. Analysis for rates were per 1, 000 hospital admissions, antibiotic days of therapy (DOT) per 1, 000 patient-days, and trends were analyzed using Cochran-Armitage tests; significance was set at P < 0.05. Results: From 2009–2016 we identified 116, 152 S. aureus hospitalizations. Patients had median age 3 (interquartile range: 0–11 years); 53.7% were male, 52.5% non-Hispanic white, and 18.8% non-Hispanic African American. From 2009 to 2016, S. aureus hospitalizations declined 36% from 26.3 to 16.8 infections per 1, 000 admissions ( P < 0.001) (figure). MRSA infections declined 52% (14.4 in 2009 to 6.9 infections per 1, 000 admissions in 2016, P < 0.001) while MSSA infections declined 17% (11.9 to 9.9 infections per 1, 000 admissions, P < 0.001). DOT for anti-MRSA antibiotics declined from 38.0 to 24.5 per 1, 000 patient-days. Conclusion: Rates of pediatric hospitalization with S. aureus infection declined substantially over time. This was largely driven by decreased rates of MRSA hospitalizations, and we observed a corresponding decline in anti-MRSA antibiotic use. Further research is needed to better understand factors driving epidemiologic changes. Figure. S. aureus hospitalization rate per 1, 000 hospital admissions in 39 PHIS hospitals with continuous reporting, 2009–2016. All S. aureus infections Disclosures: R. Banerjee, Accelerate Diagnostics, Biomerieux, BioFire: Grant Investigator, Research grant and Research support. S. Patel, Merck: Grant Investigator, Grant recipient and Research grant. Pfizer: Grant Investigator, Research grant.